Penerapan Hukuman Mati di Indonesia dan Implikasi Pedagogisnya - Yohanes S Lon (Kertha Wicaksana, 2020)
This study aims to discuss the pedagogical and pastoral implications of the application of the death penalty in Indonesia. This study uses a literature study method by presenting a discussion of the issue of the imposition of the death penalty in Indonesia and its implications for pedagogical activities. Anasilis results show that the application of the death penalty is contrary to human rights, specifically the right to life. Capital punishment authorizes external parties and human institutions to negate or revoke a person's right to life. It betrays the inherent and inseparable nature of the right to life of a human being. The right to life is accepted since a person becomes a human. So when the death penalty is applied in Indonesia, there is a perception that the government or state seems to legalize acts of violence against human rights. Such a perception can justify every act of violation of human rights of everyone. Consequently, the state is responsible for eliminating such perceptions by protecting Indonesian children from mistaken or wrongful understanding of human rights as a result of the imposition of the death penalty. For this reason, the government needs to encourage and develop proper human rights education in schools, namely education that enables students to have a correct understanding of human rights and capital punishment, love human rights values, and behave according to human rights values. Such education should be based on freedom, equality, democracy and tolerance in pluralism.